Desenvolvimento e políticas públicas: uma análise do pronaf investimento e custeio no município de Passos (MG) - Oliveira, Ana Paula Brito Silveira (2021)
The interest of this work is to deepen the socioeconomic issue experienced by rural producers, seeking to incorporate the complexities that are and may become part of the execution of a public policy, in this case, Pronaf. For Maes (2006), access to credit services is a way to provide small entrepreneurs with the means to play an active role in the economy. Credit initiatives aimed at small borrowers have been increased in countries with the aim of increasing accessibility for people outside the traditional financial system. The objective of the research was to evaluate the effectiveness of the National Program for Strengthening Family Agriculture, from the perception of family farmers in the municipality of Passos (MG), in the cost and investment modality. We used, as a methodological strategy, qualitative research of descriptive exploratory nature, carried out through field research. After observing the statements, three analytical categories emerged: "Basic socio-productive characterization of the interviewed families", "Impact of Pronaf on the lives of producers" and "Possible scenarios, challenges and expectations of family farming in Passos", through which we analyzed the questionnaires carried out with rural producers. In addition to the analytical categories, and also based on the discourses extracted from the producers, it was possible to observe, in a more tenuous way, some thematic axes (nine), which, regardless of not generating sufficient convergence for a more categorized analysis, were fundamental for the construction of the general notes. The history of the farmers highlighted here is not limited to data or numbers that prove or show improvements or contributions that Pronaf has generated in the lives of these producers, but also reflects the challenges faced.